Seismic design of reinforced concrete buildings - Moehle, Jack P. (McGraw-Hill's AccessEngineering., 2015)
With an emphasis on the American Concrete Institute standards, this in-depth resource provides comprehensive coverage of the behavior, design, and construction requirements for earthquake-resistant concrete buildings.